Effect of nanoclay addition and chemical treatment on static and dynamic mechanical analysis of jute fibre composites - Arulmurugan,Seetharaman (2019)
Abstract In this article, the influence of alkali treatment and addition of montmorillonite nanoclay as filler on mechanical and visco-elastic behaviour of jute fibre polymer composite were investigated. The composites are fabricated using 5wt% of nanoclay, untreated and chemically treated jute fibre of various percentage by handlayup method. The static mechanical properties like tensile, flexural, impact and inter laminar shear strength are studied as per respective ASTM standard. The dynamic mechanical analysis was carried out to evaluate storage modulus and damping factor of the prepared composite. The composition and structure of the functional groups of modified fibres were examined by Fourier transform infrared spectroscopy. The results showed that the interaction of filler addition and NaOH+KMnO4 treatment of fibres have significantly improved the tensile, flexural and impact properties to 47.12, 201.13, 172.61MPa respectively. Dynamic mechanical analysis results revealed that the incorporation of filler increases the storage modulus and glass transition temperature. The incorporation of 5wt% clay and 25wt% jute fiber increase the glass transition temperature of the composite material from 109 to 115 °C.